Reliability of Thai Version of Oswestry Questionnaire for the Evaluation of Low Back Pain Patients - Sae-jung, Surachai; Hunzavong, Torkamol; Jirarattanapochai, Kitti (Srinagarind Medical Journal, 2013)
Background : Low back pain is the common orthopaedic complaint. The Oswestry questionnaire has become one of the principal low back pain outcome measurement that commonly used worldwide such as America and Europe.We developed the Thai version of Oswestry questionnaire to use in Thai culture that differ from the others. Reliability of the Thai version of Oswestry questionnaire has never been reported. So we test an internal consistency using Cronbach’s alpha and item-scale correlation as the reliability of the questionnaire for the usefulness in clinical studies or the future researches. Objective : To evaluate the reliability of the Thai version of Oswestry questionnaire for assessing the Thai low back pain patients. Design : Prospective descriptive study Setting : Srinagarind hospital, Khon Kaen University Subjects : The 63 low back pain volunteers were classified to 2 groups. The first 30 patients had only low back pain and the second 33 patients had low back pain associated with leg pain. These patients complete the Thai version of Oswestry questionnaire by themselves. For patients who cannot read, we read the questionnaire step by step for their answers. Results : The results demonstrated that Chronbach’s alpha of every aspect of the questionnaire exceeded 0.7 and all inter-item correlation exceeded 0.4. Conclusions : The Thai version of Oswestry disability questionnaire is a valuable tool in assessing clinical symptoms and clinical researches in Thai patients with low back pain.